(untitled) (Research, Society and Development, 2020)
The services sector plays an important role in the economy. It is present in several organizations, either public or private, small or large, all of them are related to the services sector, to a greater or lesser extent. That being said, this work aims to evaluate a university restaurant’s quality services under the users’ perspective. A descriptive quantitative approach was adopted, and the obtained data were analyzed according to statistical analysis. The target audience was composed of students who attended the university restaurant. The simple random sampling technique was applied to collect data from 200 respondents. An adaptation of the SERVQUAL customer perception tool was used, a questionnaire was applied to restaurant users in order to evaluate their expectations and perceptions regarding the services. In general, users’ expectations exceeded the performance of services, highlighting the existence of gaps for all items analyzed. Thus, as a result of the evaluation of the university restaurant, there are pieces of evidence that users do not have a good perception regarding the quality of services. It is necessary that the restaurant’s management committee develop strategies to better meet the needs of its users.